Cross sectional study of 13 leptospira serovars in a Colombian dairy region - Olivera, Marta; Chaparro, Jenny J.; Chaparro, Yanira; Piedrahita, Diego; Fernández-Silva, Jorge; Londoño, Julián; Palacio, Luis G.; Ramírez-Vásquez, Nicolás; Villar, David (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Leptospirosis in cattle is recognized as a major cause of reproductive loses due to abortions, early embryonic death, and infertility. The type of Leptospira serovars that are currently circulating in Colombian herds is largely unknown due to the lack of national reports. Objective: The prevalence of antibodies specific to 13 Leptospira spp serovars was investigated in unvaccinated cows from 26 herds in San Pedro de los Milagros (Province of Antioquia) dairy region. Methods: Microscopic agglutination test was used on serum samples, following WHO recommendations. Results: A total of 112/900 (12.4%) of the animals had antibody titers of 1:100 or greater to at least one Leptospira serovar. Of those positive, 34/900 (3,8%) animals seroconverted to two or more serovars. In order of decreasing prevalence, the serovars detected were: hardjo prajitno, pomona, grippotyphosa, tarassovi, copenhageni, canicola, cellodeni and bratislava. There were 28 animals seropositive to serovar hardjo. Conclusion: Our results indicate that leptospirosis should be included as a differential diagnosis for various reproductive problems in this region.